Development of an evidence‐informed in‐home family services model for families and children at risk of abuse and neglect. Issue 2 (16th January 2013) - Ingram, Stephanie D.; Cash, Scottye J.; Oats, Robert G.; Simpson, Amy; Thompson, Ronald W.
Abstract This paper describes the components of a programme designed to prevent child maltreatment which includes the promising practices of a continuous engagement process, cognitive‐behavioural parent and skill teaching, and development of formal and informal supports for families. The programme was also designed to be implemented wide scale. Methods for assessment of strengths and needs, individualization of goals and intervention strategies, and assessment of goal achievement are also described. Finally, preliminary results of a programme implementation fidelity and outcome evaluation are summarized. The authors conclude that this programme is ready for a more rigorous efficacy trial to continue to build the evidence base for this promising intervention addressing a prevalent social problem.